Deadly craft; fireships to PT boats - Hoyt, Edwin P. (Edwin Palmer), 1923-2005.; Geer, Charles (Boston, Little, Brown, 1968)
A history of small warships from ancient Egyptian ramming boats and Greek fireships to modern PT boats, including many accounts of their use in specific battles.
"An Atlantic Monthly Press book."
Bibliography: p. [151]
Keywords: Torpedo-boats.; Warships; Torpedo boats; Warships